1997
DOI: 10.1093/ageing/26.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and disability in elderly Zimbabweans

Abstract: this study highlights problem areas where simple, low-cost measures could make a difference to the morbidity and disability of elderly Zimbabweans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 10 publications
2
36
1
4
Order By: Relevance
“…They argue that the number of children and their characteristics such as gender, marital and economic statuses may affect their ability to support older people. However, research on poverty among older people has provided an understanding of its consequences beyond the lack of physical necessities, income and material assets (Chambers, 1995;1997). Illiteracy, unemployment, powerlessness and physical weakness due to malnutrition and illness are often concomitant of poverty and lack of support for older people.…”
Section: Kin Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…They argue that the number of children and their characteristics such as gender, marital and economic statuses may affect their ability to support older people. However, research on poverty among older people has provided an understanding of its consequences beyond the lack of physical necessities, income and material assets (Chambers, 1995;1997). Illiteracy, unemployment, powerlessness and physical weakness due to malnutrition and illness are often concomitant of poverty and lack of support for older people.…”
Section: Kin Availabilitymentioning
confidence: 99%
“…The rural sample of 174 respondents was from Maramba, Pfungwe and Uzumba, in North Eastern Zimbabwe covering an area of 2646 km (CSO, 1969 quoted in Allain et al, 1997). The rural area's farthest point from the capital city of Zimbabwe, Harare, is 245 kilometers and its nearest point from Harare is 120 kilometers.…”
Section: Sampling Designmentioning
confidence: 99%
“…In addition, among women, the prevalence of undernutrition was highest in the oldest age-group which is indicative of a worsening situation with advancing age but could also be an indication of worsening health which may have a signi®cant in¯uence on the nutritional status of older people. Malaria and respiratory diseases are the common causes of morbidity among all ages in Malawi (GOM/UN, 1993) but joint and muscular pain tends to be more prevalent among older people (Allain et al, 1997). Chronic illnesses which are prevalent among older people may have a bearing on their nutritional status particularly if they remain undiagnosed and therefore untreated.…”
Section: Nutritional Indicatorsmentioning
confidence: 99%
“…In Africa, studies on the well being of older people are now emerging (Allain et al, 1997;Aspray et al, 1996;Angura & Anyuru, 1994;Coombes et al, 1994;Nmadu, 1994;Matuja et al, 1994;McLigeyo, 1993;Wilson et al, 1991;Olubuyide et al, 1991;Apt, 1990;Pappoe et al, 1990;Hampson, 1985;Waterston, 1982;Drury, 1972) but most lack crucial nutrition data. More recently, the nutritional status of older people has been assessed in Africa (Ethangatta et al, 1996;Thoner, 1993;Aspray et al, 1994), but the studies did not consider alternatives to measurement of height.…”
Section: Introductionmentioning
confidence: 99%
“…A "nutrition team" would improve the dentition and diet of those at risk. A recent community-based study in Zimbabwe identified movement, sight and nutrition as major factors where simple process-based interventions would yield sub stantial benefit (Allain, Wilson et al, 1997). Yet there is no evidence to date that such simple interventions have been translated into health-service policy.…”
Section: Health Care Processmentioning
confidence: 99%